Rice Market Integration in Kubu Raya Regency, West Kalimantan, Indonesia - Fitriana Aini; Erlinda Yurisinthae; Maswadi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
As a primary staple food, rice constitutes a strategic commodity within Indonesia's economy. Its price stability directly influences national inflation, farmer welfare, and household purchasing power. Despite being a significant rice-producing region, Kubu Raya Regency in West Kalimantan experiences persistent price fluctuations that contribute to market inefficiency. This study investigates the integration between producer and consumer rice markets by applying Vector Autoregression (VAR) and Vector Error Correction Model (VECM) methodologies. Analyzing price series data from 2015 to 2020, sourced from Statistics Indonesia (BPS) and the National Logistics Agency (Bulog), we find that all variables are stationary at level, justifying the use of a VAR model. The Akaike Information Criterion (AIC) selected lag 1 as optimal, and stability tests confirmed the model's validity. The Johansen cointegration test reveals two cointegrating vectors, indicating a significant long-run equilibrium relationship between producer and consumer prices. However, estimates from the VAR model and results from the Granger causality test demonstrate ineffective short-term price transmission. We attribute this market segmentation to structural inefficiencies within the distribution chain and the weak bargaining power of farmers. Consequently, we recommend that regional policy interventions prioritize strengthening farmer institutions, enhancing the transparency of price information systems, and streamlining distribution logistics to foster more integrated and efficient local rice markets.